The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.joc.7b02415
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated BOPHY Dyes: Synthesis, Reactivity, and Properties

Abstract: A series of mono- to hexabrominated BOPHY dyes have been regioselectively synthesized in 41-96% yields from bromination of parent bis(difluoroboron)-1,2-bis((1H-pyrrol-2-yl)methylene)hydrazine (BOPHY), bromination of hydrazine-linked bispyrrole intermediate, or brominated 2-formylpyrrole precursors in moderate to excellent yields. The reactivities of these polybrominated BOPHY dyes were further studied via regioselective nucleophilic substitution or Suzuki/Stille cross-coupling reactions from which a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 71 publications
3
41
0
Order By: Relevance
“…BOPHY 10 is the first di‐substituted dipyrrolyl‐BOPHY reported, with the most bathochromically shifted absorption and emission of this type of compound. This is in agreement with previous investigations of pyrrolyl‐based substituents at the 3,5‐positions of BODIPY or 3‐position of BOPHY, as an effective method to shift their absorption and emission wavelengths to the near‐IR region [7a,19] …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…BOPHY 10 is the first di‐substituted dipyrrolyl‐BOPHY reported, with the most bathochromically shifted absorption and emission of this type of compound. This is in agreement with previous investigations of pyrrolyl‐based substituents at the 3,5‐positions of BODIPY or 3‐position of BOPHY, as an effective method to shift their absorption and emission wavelengths to the near‐IR region [7a,19] …”
Section: Resultssupporting
confidence: 92%
“…Treatment of BOPHY 1 with 10 equivalents of bromine in chloroform [7a,19] led to the formation of 3,8‐dibrominated BOPHY 2 in 72 % yield, as shown in Scheme 1. BOPHY 2 was recrystallized from dichloromethane/methanol and directly used in reactivity studies, as shown in Schemes 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase of the fluorescence for the diprotonated species [aza‐BODIPY+2H + ], in comparison with the weakly fluorescent monoprotonated form [aza‐BODIPY+H + ] and the nearly non‐emissive neutral 6 , is associated with the inhibition of the intramolecular charge transfer (ICT). These preliminary results indicate that compounds presented in this paper could operate as a novel potential “turn‐on” pH sensors where protonation of the NMe 2 groups alleviates ICT and increases the fluorescence quantum yield (φ fl ) …”
Section: Resultsmentioning
confidence: 73%
“…Compounds 5 to 8 , due to the presence of dimethylamino groups (Me 2 N‐), proved to be sensitive to the pH value . Exemplarily, toluene solution of aza‐BODIPY 6 upon titration with trifluoroacetic acid (TFA, Figure ) showed a stepwise disappearance of the absorption band at λ abs 675 nm with the concomitant evolution of a blue‐shifted absorption band at λ abs 660 nm, meaning formation of a fully protonated form of 6 , viz.…”
Section: Resultsmentioning
confidence: 99%